Escape and evolution of Mars's CO2 atmosphere: Influence of suprathermal atoms. Issue 6 (17th June 2017) - Amerstorfer, U. V.; Gröller, H.; Lichtenegger, H.; Lammer, H.; Tian, F.; Noack, L.; Scherf, M.; Johnstone, C.; Tu, L.; Güdel, M.
Abstract: With a Monte Carlo model we investigate the escape of hot oxygen and carbon from the Martian atmosphere for four points in time in its history corresponding to 1, 3, 10, and 20 times the present solar EUV flux. We study and discuss different sources of hot oxygen and carbon atoms in the thermosphere and their changing importance with the EUV flux. The increase of the production rates due to higher densities resulting from the higher EUV flux competes against the expansion of the thermosphere and corresponding increase in collisions. We find that the escape due to photodissociation increases with increasing EUV level. However, for the escape via some other reactions, e.g.,  dissociative recombination of O 2 +, this is only true until the EUV level reaches 10 times the present EUV flux and then the rates start to decrease. Furthermore, our results show that Mars could not have had a dense atmosphere at the end of the Noachian epoch, since such an atmosphere would not have been able to escape until today. In the pre‐Noachian era, most of the magma ocean and volcanic activity‐related outgassed CO2 atmosphere could have been lost thermally until the Noachian epoch, when nonthermal loss processes such as suprathermal atom escape became dominant. Thus, early Mars could have been hot and wet during the pre‐Noachian era with surface CO2 pressures larger than 1 bar during the first 300 Myr after the planet's origin. Key Points: Escape of suprathermal atoms from Mars's atmosphere with increasing EUV flux is studied Mars could not have had a dense atmosphere at the end of the Noachian epoch Mars's surface pressure could have been larger than 1 bar during the first 300 Myr after the planet's origin